Nursing care evaluation: peripherally inserted central catheter dressings in newborns. - Johann, Derdried Athanasio; Danski, Mitzy Tannia Reichembach; Pedrolo, Edivane; DeLazzari, Luciana Souza Marques; Mingorance, Priscila (Revista Mineira de Enfermagem)
This research aimed to describe the PICC (Peripherally Inserted Central Catheter) dressings in newborns and to analyze its use with the available literature on the subject. A descriptive and comparative method was used by data collection form to the systematic observation of nurses trained in PICC insertion and maintenance in an Intensive Care Unit at a University Hospital from March to May 2008. Ten dressings were analyzed; two after insertion and eight at maintenance. The dressings were performed according to aseptic technique and did not have complications. However the standard operating procedure for this practice was not based on the published meta-analysis nor were the professionals aware of the evidence presented in there. In conclusion the study demonstrated that the scientific information on such procedure is not frequently applied by the professionals involved directly with patient care.